Stability of wafer-scale thin films of vertically aligned hexagonal BN nanosheets exposed to high-energy ions and reactive atomic oxygen - Huang, Shiyong (2023)
Stability of advanced functional materials subjected to extreme conditions involving ion bombardment, radiation, or reactive chemicals is crucial for diverse applications. Here we demonstrate the excellent stability of wafer-scale thin films of vertically aligned hexagonal BN nanosheets (hBNNS) exposed to high-energy ions and reactive atomic oxygen representative of extreme conditions in space exploration and other applications. The hBNNS are fabricated catalyst-free on wafer-scale silicon, stainless steel, copper and glass panels at a lower temperature of 400 °C by inductively coupled plasma (ICP) assisted chemical vapor deposition (CVD) and subsequently characterized. The resistance of BNNS to high-energy ions was tested by immersing the samples into the plasma plume at the anode of a 150 W Hall Effect Thruster with BNNS films facing Xenon ions, revealing that the etching rate of BNNS is 20 times less than for a single-crystalline silicon wafer. Additionally, using O2/Ar/H2 plasmas to simulate the low Earth orbit (LEO) environment, it is demonstrated that the simulated plasma had very weak influence on the hBNNS surface structure and thickness. These results validate the strong potential of BNNS films for applications as protective, thermally conductive and insulating layers for spacecrafts, electric plasma satellite thrusters and semiconductor optoelectronic devices.